Detection and compensation of anomalous conditions in a wind turbine. (1st April 2017) - Hur, S.; Recalde-Camacho, L.; Leithead, W.E.
Abstract: Anomalies in the wind field and structural anomalies can cause unbalanced loads on the components and structure of a wind turbine. For example, large unbalanced rotor loads could arise from blades sweeping through low level jets resulting in wind shear, which is an example of anomaly. The lifespan of the blades could be increased if wind shear can be detected and appropriately compensated. The work presented in this paper proposes a novel anomaly detection and compensation scheme based on the Extended Kalman Filter. Simulation results are presented demonstrating that it can successfully be used to facilitate the early detection of various anomalous conditions, including wind shear, mass imbalance, aerodynamic imbalance and extreme gusts, and also that the wind turbine controllers can subsequently be modified to take appropriate diagnostic action to compensate for such anomalous conditions. Highlights: An anomaly detection and compensation scheme for a wind turbine based on the Extended Kalman Filter is proposed. Various anomalies, including wind shear, blade mass imbalance and gusts, can be detected and timely compensated. Unnecessary shut-downs can be avoided, resulting in increased energy production and grid protection. Loads on the turbine can be mitigated, resulting in reduced operations and maintenance costs or life-time extension.